EFFECTIVENESS OF DRUG PREPARATIONS AGAINST FISH NEMATODOSIS - Bazarbayeva Karomat S.; Soliyeva Gulnoza D.; Amirov Oybek O.; Sarvar S. Saidov; Bazarbayev Shavkat S. (Web of Journals Publishing, 2025)
The purpose of this research is to study the effect of Albendazole 10% and the anthelmintic drugs 2-propidamisole (powder), 2-acetamisole (powder) developed by scientists at the Institute of Plant Chemistry of the Academy of Sciences of the Republic of Uzbekistan on nematodes of the gastrointestinal tract of fish
Keywords: Albendazole, Propydamisole, Acetamisole, Anthelmintic, Stomach, Intestines, Nematodes.